P1 Antiphospholipid syndrome in qatar: epidemiological, clinical, and immunological characteristics. (23rd March 2020) - Abdulla, Nabeel; Alsaed, Omar; Alam, Fiaz; Saleh, Rawan; Poil, Abdulrazzakh; Siam, Abdelrahim; Elsayed, Eman; Abdulaziz, Hani; Emadi, Samar Al
Abstract : Purpose: The aim of this study is to analyze epidemiological, clinical, and immunologic characteristics of primary and secondary antiphospholipid syndrome (APS) cases in Qatar. Methods: All patients with primary and secondary APS attending rheumatology clinics from January 2017 to May 2019 at Hamad General Hospital were identified and medical records were retrospectively reviewed. Results: 131 patients with APS who fulfilled revised Sapporo APS classification criteria were included- 116 women (88.5%) and 15 men (11.5%). 79 patients (60.3%) had primary and 52 patients (39.7%) had secondary APS. 41 patients (31.3%) had thrombotic event only, 64 patients (48.9%) had pregnancy morbidity only, and 26 patients (19.8%) had both thrombosis as well as pregnancy morbidity. 7 patients (5.4%) had arterial thrombosis only, 48 patients (36.6%) had venous thrombosis only and 12 patients (9.1%) had both arterial and venous thrombosis. 103 (78.6%) patients had pregnancy morbidity out of the 116 female patients. Early fetal loss was the commonest pregnancy morbidity seen in 73 patients (70.9%), followed by late fetal loss in 57 patients (55.3%). 48 patients (36.6%) had aCL IgG positive and 15 patients (11.5%) had aCL IgM positive, either one was positive in 54 patients (41.2%). 42 patients (32.1%) had B2GP IgG positive and 19 patients (14.5%) had B2GP IgM positive, either one was positive in 53 patients (40.7%). LA was positive in 121 patients (92.4%). There were 71 patients (54.2%) with single positive aPL test, 21 patients (16%) with double positive and 37 patients (28.2%) with triple positive aPL test results. LA was the most common single positive aPL test, seen in 65 patients (50.3%) Conclusion: The clinical manifestation and immunological characteristics of patients with APS in Qatar are diverse. Our cohort has much higher prevalence of LA positivity compared to other cohorts around the world. We also have a higher incidence of pregnancy morbidities. Acknowledgements: Study funded by Medical research center at Hamad Medical Corporation.